Compliment Responses of The Main Characters in Indonesian and American Movies - Widiningrum, Rindang (State institute of islamic studies salatiga, 2020)
Movies can be said as a reflection of real life. This study is aimed at finding the compliment responses by the main characters in two movies. The movies are 'Mars Met Venus' and 'Hitch'. The data were taken from the utterances of the main characters, both are male and female, that were considered as compliments' responses. The topics of the compliments in those two movies are appearance, ability, personality, and possession. The finding resulted in this research showed that there were 20 compliment responses found in those movies. There are silent, return, questioning, reassignment of praise, explaining, shifting to other topics, appreciation, and agree. In 'Mars met Venus, there are silent (3 times), returns (3 times), questioning (3 times), reassignment of praise (1), and explaining (1). While in 'Hitch', there are shifting to other topics (4 times), appreciation (1), explaining (1), questioning (2 times), and agree (1). Based on those, it can be concluded that questioning (25%) got the highest percentage, then shifting to other topics (20%), silent (15%), return (15%), explaining (10%), agree (5%), reassignment of praise (5%) and appreciation (5%). Questioning as the highest percentage in these movies shows that the person being complimented needs more explanation about the compliment. In comparison, there are similarities and differences from those movies. Those differences are the reflections of different cultures represented by the two movies. Keywords: pragmatics, movie, compliment response.